Blood Transfusion cross match on the basis of Phenotype & Rh Antigen in Donors and Receivers and Analysis of Variations - Muhammad Faisal Aslam, Khadeeja Khan, Javeria Ghafoor, Muhammad Immran, Nimrah Ishaque, Ashja Saleem, Maheen Rana, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: In brief, knowing the local Rh blood group system frequency helps develop a donor pool for patients who need numerous transfusions and alloantibody-compatible antigen negative blood. Patients have been matched for component blood transfusions using ABO and Rh phenotypes since 2020. Our detection of all blood transfusion-needy patients began. Aim: Our department began To detect C, E, c, and e Rh-specific antigens in multi-transfused patients in 2020. Methods: For the aim of this investigation, 2300 patient samples were obtained from patients who required clinical blood transfusions at our hospital between March 2020 and October 2022. These samples were gathered for the purpose of this investigation. One patient was counted as a single sample even though they required repeated blood transfusions. 1900blood donor samples were provided by the Blood Centre of (duplicated samples were removed based on the identification numbers that were provided by the Blood Centre once they were identified). Results: The study obtained 4200 samples, including 1900donor and 2300patient samples. The allele frequency distribution of blood group antigens in the studied population was compared with the prevalence observed in the present study. The D antigen exhibited a frequency of 99.34% in the studied population, slightly lower than the prevalence observed in the present study at 98.9% (95% CI: 98.5 - 99.0). Conversely, the C antigen was found in 93.1% of the studied population, with a slightly higher prevalence observed in the present study at 99.1% (95% CI: 92.0 - 99.2). Implication: The study suggests serological testing is a cost-effective method for blood transfusion management, identifying Rh phenotypes. Compiling a database of donor Rh genotypes simplifies transfusion selection, reducing unfavorable responses. Pre-transfusion Rh phenotype examination is crucial for matching patient blood type with donor blood, reducing adverse reactions, and improving patient safety. Conclusion: In transfusion applications, serological testing are cost-effective for Rh phenotype identification but not genotypes. Creating a database of blood donors' Rh phenotypes and evaluating each patient before their initial transfusion should lessen adverse reactions and speed up antigen-negative blood availability, saving more patients. Keywords: Blood transfusion, phenotype, Rh antigen, donors, receivers, analysis of variations